2001
DOI: 10.1139/g00-096
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellite markers in potato and their use in phylogenetic and fingerprinting analyses

Abstract: Three genomic libraries were constructed using a mixture of DNA from Solanum phureja Juz. & Buk., and S. chacoense Bitt. Two of the libraries were enriched for ATT and GT repeats (a 27-fold enrichment was achieved). In total, 3500 clones of the conventional library, 1,000 of the library enriched for ATT, and 12,000 of the one enriched for GT were screened with five different repeat motifs, and a total of 18 primer pairs was obtained. Another group of 12 primer pairs was obtained from the SSR-containing sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 56 publications
(58 reference statements)
3
56
1
2
Order By: Relevance
“…Several other studies have also reported the high incidence of AT-based repeats in tomato (Smulders et al 1997;Areshchenkova and Ganal 2002;Suliman-Pollatschek et al 2002;He et al 2003), potato (Ashkenazi et al 2001), and other plants (Morgante and Olivieri 1993;Wang et al 1994). In addition, the present study identified a considerable proportion (25%) of compound or mixed repeats.…”
Section: Survey Of Ssrs For Polymorphism Across Tomato Varieties and mentioning
confidence: 88%
“…Several other studies have also reported the high incidence of AT-based repeats in tomato (Smulders et al 1997;Areshchenkova and Ganal 2002;Suliman-Pollatschek et al 2002;He et al 2003), potato (Ashkenazi et al 2001), and other plants (Morgante and Olivieri 1993;Wang et al 1994). In addition, the present study identified a considerable proportion (25%) of compound or mixed repeats.…”
Section: Survey Of Ssrs For Polymorphism Across Tomato Varieties and mentioning
confidence: 88%
“…Sin embargo, los más utilizados y aceptados han sido los SSRs (Single Sequence Repeat) o microsatélites (Schneider y Douches, 1997;Ashkenazi et al, 2001;Ghislain et al, 2001b;Norero et al, 2003). Los SSRs presentan mayor simplicidad tecnológica en relación a RFLP y AFLP, y no requieren alta concentración y calidad de ADN.…”
Section: Introductionunclassified
“…Another important point is that the DNA sequences flanking the SSRs are conserved within the same species, allowing the selection of specific primers that amplify via PCR. The amplification using a pair of primers complementary to unique sequences that flank, resulting in an enormous fragment length polymorphism This size variation of PCR products is a consequence of the occurrence of different numbers of repeating units within structure of microsatellites (Ashkenazi et al, 2001;Cregan et al, 1999a;McCouch et al, 1997;Morgante & Olivieri, 1993). Thus, alleles may be determined for a given population.…”
Section: Microsatellites -Ssr (Simple Sequence Repeat)mentioning
confidence: 99%